Understanding Consumer Trust Formation in Social Commerce: The Impact of Influencer Credibility and Algorithmic Transparency - Aarav R. Sharma (Vifada Management and Social Sciences, 2025)
This study investigates how consumer trust is formed in social commerce environments through two primary drivers: influencer credibility and algorithmic transparency. As social commerce increasingly shapes online purchasing behavior, understanding the psychological mechanisms behind trust becomes essential for digital marketers, platforms, and businesses. Using a quantitative approach with 412 respondents from active social commerce users, the findings reveal that influencer credibility—comprising expertise, authenticity, and social attractiveness—significantly enhances consumer trust and purchase intention. Furthermore, algorithmic transparency, including clarity of recommendation logic and perceived fairness of content distribution, moderates the relationship between influencer credibility and trust formation. The results underscore the importance of transparent platform practices and credible influencer partnerships in improving consumer confidence and reducing perceived risk. This research contributes to the growing literature on digital trust-building while offering practical insights for social commerce platforms to design more ethical, transparent, and user-centered recommendation ecosystems.